A Study on Awareness of Mutual Fund Investment (With Special Reference to Kottayam District) (International Journal of Scientific Research in Science and Technology, 2024)
This study investigates awareness levels in mutual fund investment with special reference to Kottayam District. The sample size of 50 respondents are collected from mutual fund investors with different demographic back grounds by using a scheduled questionnaire. This study explores demographic factors of mutual fund investors in Kottayam and study the investors awareness regarding mutual fund investment. This study reveals that male respondents from rural areas of Kottayam with 50 years and above age having post-graduation invest more money in mutual funds than all other respondents. The awareness about the different aspects of mutual fund investment is not enough to make a successful investment strategy to the investors from Kottayam. By conducting awareness programs and financial literacy programs can improve their knowledge in mutual fund investment.